Simulation & visualization of drone movements in virtual tower simulator - Nur Syamirah Mohamed Ali (Nanyang Technological University, 2021)
The purpose of this project is to provide videos of UAVs in flight at a simulated airport environment to advance in the research of drone detection methods. NLR Air Traffic Control Research Simulator (NARSIM) is an air traffic research simulator that is able to simulate most important aspects of a real air traffic control system. For this purpose, NARSIM is pre-installed with details of common objects within the airport environment. The conditions when running NARSIM simulation is primarily through the controls within the system. However, when drones are introduced into the system for future research, a different approach has to be implemented. This is due to the server specification file -.xml extension files -that simulator requires to be input into the system, in order for simulation to work. To replicate drone intrusions into the airport, the trajectory of the intruder has to be manipulated to provide a randomized motion of the drone when infiltrating into the safe airspace of Changi International Airport on NARSIM Flight Simulator. This was achieved through implementing existing functions available in the NARSIM system into the XML file used to run the simulation. Handcrafting of scripts foraircraft and/or drone trajectory is time-consuming and requires repetitive efforts despite having the same commands throughout the script. Difficulties in automating the script writing process negatively impacted the progress of this project. Nonetheless, this report is still valid to provide a baseline to progress in the development of this project.